A review on plant-mediated synthesis of silver nanoparticles, their characterization and applications. (31st May 2021) - Chandraker, Sandip Kumar; Ghosh, Mithun Kumar; Lal, Mishri; Shukla, Ravindra
Abstract: For decades, silver has been used as a non-toxic inorganic antimicrobial agent. Silver has a lot of potential in a variety of biological/chemical applications, particularly in the form of nanoparticles (NPs). Eco-friendly synthesis approach for NPs are becoming more common in nanobiotechnology, and the demand for biological synthesis methods is growing, with the goal of eliminating hazardous and polluting agents. Cultures of bacteria, fungi, and algae, plant extracts, and other biomaterials are commonly used for NP synthesis in the 'green synthesis' process. Plant-based green synthesis is a simple, fast, dependable, cost-effective, environmentally sustainable, and one-step method that has a significant advantage over microbial synthesis due to the lengthy process of microbial isolation and pure culture maintenance. In this report, we focussed on phytosynthesis of silver nanoparticles (AgNPs) and their characterization using various techniques such as spectroscopy (UV–vis, FTIR), microscopy (TEM, SEM), X-Ray diffraction (XRD), and other particle analysis. The potential applications of AgNPs in a variety of biological and chemical fields are discussed.